(untitled) (Law, State and Telecommunications Review, 2019)
Purpose ”“ Economic activity is based increasingly on the Internet. This development generates multiple benefits for consumers but also competition challenges for operators and regulatory authorities. Methodology/approach/design ”“ The study considers the recent evolution of the traditional voice, messaging and video telecommunications services, as well as OTT of similar functionality that coexist in the markets with them. Based on the literature review, the degree of substitution and / or complementarity between traditional services and OTT is analyzed from a demand perspective. Findings ”“ No conclusions can be set, as certain conditions of consumption substitution is observed, while in others, complementarity between services. From the perspective of suppliers, there is a certain complementarity that is reflected in a greater number of associations between operators and OTT.